The New Complex Integral Transform "Complex Sadik Transform" and It’s Applications - M. Turq, Saed; A. Kuffi, Emad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
In this paper, we introduce a new complex integral transform namely ”Complex Sadik Transform”. The properties of this transformation are investigated. This complex integral transformation is used to reduce the core problem to a simple algebraic equation. The answer to this primary problem can than be obtained by solving this algebraic equation and applying the inverse of complex Sadik transformation. Finally, the complex Sadik integral transformation is applied and used to find the solution of linear higher order ordinary differential equations. As well as, we present and discuss, some important real life problems such as: pharmacokinetics problem ,nuclear physics problem and Beams Probem